2012
DOI: 10.1371/journal.pone.0051030
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of the Serine-Arginine Protein Kinase 1 Gene in Ovarian Cancer and Its Role in Cisplatin Cytotoxicity In Vitro

Abstract: Alternatively spliced variants of several oncogenes and tumor suppressors have been shown to be important for their tumorigenicity. In the present study we have tested whether serine-arginine protein kinase 1 (SRPK1), a major regulator of splicing factors, is involved in ovarian cancer progression and plays a role in chemo-sensitivity. By Western blot analyses, SRPK1 protein was found to be overexpressed in 4 out of 6 ovarian cancer cell lines as compared with an immortalized ovarian surface epithelial cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 34 publications
1
42
0
7
Order By: Relevance
“…Our observation agrees with reduced SRPK1 expression in certain cancer cell lines (Hayes et al, 2006) or tumors (Krishnakumar et al, 2008; Odunsi et al, 2012; Schenk et al, 2004). Examination of a panel of human colon cancers revealed that SRPK1 was undetectable in multiple tumors compared to surrounding non-cancerous tissues (Figure 2D).…”
Section: Resultssupporting
confidence: 89%
“…Our observation agrees with reduced SRPK1 expression in certain cancer cell lines (Hayes et al, 2006) or tumors (Krishnakumar et al, 2008; Odunsi et al, 2012; Schenk et al, 2004). Examination of a panel of human colon cancers revealed that SRPK1 was undetectable in multiple tumors compared to surrounding non-cancerous tissues (Figure 2D).…”
Section: Resultssupporting
confidence: 89%
“…31 siRNA mediated silencing of SRPK1 in ovarian cancer cell lines resulted in reduced cell proliferation and increased sensitivity to cisplatin. 34 Inhibition of SRPK1 using siRNA or pharmacological inhibitor suppressed VEGF expression and decreased melanoma growth in vivo. Studies by Zhou et al, have shown that SRPKs constitute a major branch of Akt signaling pathway in EGF mediated alternate splicing.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the intracellular level of SRPK1, a major kinase of SR proteins, has been demonstrated to be critical in the regulation of the alternative splicing profile of malignant cells (Gout et al 2012;Odunsi et al 2012;. Mutations of Wilms' tumor suppressor gene (WT1) lead to the up-regulation of SRPK1, which diminishes the SRSF1-mediated up-regulation of VEGF165b (Amin et al 2011).…”
Section: Discussionmentioning
confidence: 99%